2018
DOI: 10.1007/s11916-018-0690-8
|View full text |Cite
|
Sign up to set email alerts
|

New Advances in Acute Postoperative Pain Management

Abstract: Over the last decade, Enhanced Recovery after Surgery (ERAS) pathways and protocols are becoming the benchmark standards for enhancing postoperative recovery. Multimodal analgesia (MMA) is an essential component of such care. Further, in the wake of serious and persistent concern on the opioid epidemic in the USA, there has been a recent renewal of interest in non-opioid alternatives or adjuncts in controlling postoperative pain, often in the context of MMA. Intravenous (IV) acetaminophen, non-steroidal anti-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(96 citation statements)
references
References 99 publications
0
87
0
9
Order By: Relevance
“…However, opioids remain the cornerstone treatment for acute postoperative pain. 21 Dale et al report that reducing opioid consumption is very important because of their side effects, such as urinary retention, pruritus, oversedation, opioid-induced hyperalgesia, respiratory depression, nausea, and vomiting. 22 Albrecht et al have shown that regional analgesia may be a crucial component of multimodal postoperative pain management to reduce perioperative opioid consumption.…”
Section: Discussionmentioning
confidence: 99%
“…However, opioids remain the cornerstone treatment for acute postoperative pain. 21 Dale et al report that reducing opioid consumption is very important because of their side effects, such as urinary retention, pruritus, oversedation, opioid-induced hyperalgesia, respiratory depression, nausea, and vomiting. 22 Albrecht et al have shown that regional analgesia may be a crucial component of multimodal postoperative pain management to reduce perioperative opioid consumption.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Briefly, PCL (100 mg) as polymer, PEG-DSPE (100 mg) as lipid, and lecithin (20 mg) as lipophilic surfactant were dissolved in acetone (5 mL) as an organic solvent to form the oil phase (1). RPV (20 mg) was dissolved in sodium dodecyl sulfate (0.5 mL, 5%, w/v) solution to form the internal aqueous phase (2). Next, solution (1) was sonicated (1 minute) in an ice-bathed solution (2) for emulsification.…”
Section: Lpns Preparationmentioning
confidence: 99%
“…Postoperative pain management remains one of the most common challenges which have been largely unmet. 1,2 Local anesthetics are used clinically for the control of pain following operation (including gastrointestinal surgery), or for the management of other acute and chronic pain. [3][4][5] However, the major limitation of local anesthetics is their short duration of action (,8 hours).…”
Section: Introductionmentioning
confidence: 99%
“…Ketamine has a clear opioid-sparing effect in the perioperative period [ 20 ] and may even reduce long-term opioid consumption in opioid-tolerant patients [ 21 ] as well as persistent postsurgical pain when used intravenously [ 22 ]. It is increasingly being featured in MMA protocols as an opioid alternative [ 23 ]. Although reviews have not consistently shown an increased incidence of side effects compared to controls [ 20 , 24 ], ketamine has the potential to cause psychomimetic effects and this should be factored into treatment decisions.…”
Section: Elements Of Multimodal Analgesiamentioning
confidence: 99%